ORIENTALISM AND POSTCOLONIAL DISCOURSE: COUPLE METHODOLOGICAL PROBLEMS - Beinorius, Audrius (Porównania, 2012)
The main inspiration for this article’s author is Edward Said’s book Orientalism and the main goal discussion over the development of the conception of the orientalism in the context of postcolonial discourse. The author pays attention to cultural and material violence of Western colonialism. At the same time he highlights the necessity of taking into account such aspects as religious pluralism and cultural variety. It can enable a creation of a communication platform between a passive East and an oppressive West.